Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1002/2013jc009278
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term upwelling events at the western African coast related to synoptic atmospheric structures as derived from satellite observations

Abstract: [1] Satellite scatterometers provide continuously valuable surface wind speed and direction estimates over the global ocean on a regular grid both in space and time. The Level 3 data derived from the Advanced Scatterometer (ASCAT), available at 1/4 spatial resolution (hereafter AS25), and Quick Scatterometer (QuikSCAT), available on 1/2 and 1/4 horizontal grids (QS50 and QS25, respectively), are studied at regional scales in both the Benguela and Canary upwelling systems. They are compared to the European Cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 51 publications
2
20
0
Order By: Relevance
“…Such phase differences have been noticed in satellite observations ) but have so far been unexplained. The lag is in contrast with EBUs dynamics where wind forcing and SSH/SST are generally in phase (Wang 1997) or lag by no more than a few days (Desbiolles et al 2014). Following a suggestion by J. McCreary in his review of an initial version of this manuscript, we propose that the lag results from the onshore propagation of long-wavelength, upwelling-favorable, Rossby waves.…”
Section: Seasonalitymentioning
confidence: 71%
“…Such phase differences have been noticed in satellite observations ) but have so far been unexplained. The lag is in contrast with EBUs dynamics where wind forcing and SSH/SST are generally in phase (Wang 1997) or lag by no more than a few days (Desbiolles et al 2014). Following a suggestion by J. McCreary in his review of an initial version of this manuscript, we propose that the lag results from the onshore propagation of long-wavelength, upwelling-favorable, Rossby waves.…”
Section: Seasonalitymentioning
confidence: 71%
“…Plans for dedicated atmospheric observations at and slightly south of the oceanic Angola-Benguela Front are still lacking. Because the ocean upwelling responds quickly to changes in the surface wind structure (Desbiolles et al 2014), assessments of fast SST error growth can potentially readily identify the importance of wind errors for the upwelling regions for individual models. A search for the commonalities across models in the upwelling regions can help narrow down the root causes.…”
Section: Gaps and Recommendationsmentioning
confidence: 99%
“…The three wind stress products are mainly upwelling-favorable during the 2-month period of analysis. In a previous study, we showed that the QS50 winds are less statistically related to the SST field than the QS25 winds and that the QS50 product most often overestimates the wind velocity in regions where the SST front is sharp (Desbiolles et al, 2014b). This sensitivity to the SST front is detectable in the average wind stress structure resulting in a broader and nearer inshore atmospheric jet in the QS50 product (see Fig.…”
Section: Wind Stress Forcing and Set Of Numerical Experimentsmentioning
confidence: 89%
“…This generates small-scale features in the low-level wind (Chelton et al, 2004;O'Neill et al, 2005;Small et al, 2008). In a previous study, we showed that the coupling between wind and SST is the main driver of both the magnitude and the variability of the wind stress curl during the upwelling season in the Benguela and Canary systems (Desbiolles et al, 2014b). SST-driven modifications to the wind contribute to a wind reduction in a transition region that may extend over 100 km offshore (Boé et al, 2011).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation